'In die begin ...': oor vertrekpunte en die verstaan van tekste - Deventer, Hans J. M. van (Koers, 2005)
'In the beginning ...': on points of departure and understanding texts This article renders a contribution to the discussion on evolution from a theological point of view. It is interested in laying bare the epistemological points of departure that are reflected in studies related to the creation-evolution debate, especially those behind recent interpretations of Genesis 1 and 2. In an argument mirroring Ricoeur’s central thesis, examples of a first naïveté when reading the creation texts in the Bible are given. Next, a few examples of recent interpretations of the creation texts are given in order to indicate the present state of knowledge in the field. Lastly, one example is given in which these results were taken serious within a faith context, that led to what can be viewed as the development of a second naïveté.